The Effect of Financial Literacy on Financial Management of High School Teachers - Irdawati; Rakhmat; Yuli Rahmini Suci; Septy Indra Santoso (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Financial literacy is vital for teachers to manage personal finances effectively and secure long-term economic stability. This study investigates the impact of basic and advanced financial literacy on the financial management of high school teachers in Makassar City. Using a quantitative descriptive approach, 100 teachers were selected through purposive sampling, and data were collected via questionnaires. SmartPLS was employed to test validity, reliability, and hypotheses. Results indicate that both basic and advanced financial literacy significantly influence financial management. Basic literacy contributes 26.6% (p = 0.017 < 0.05), while advanced literacy shows a stronger effect of 61.6% (p = 0.000 < 0.05). Together, the two variables explain 68.1% of the variation in financial management, with 31.9% influenced by other factors. These findings highlight the dominant role of advanced financial literacy in shaping effective financial practices, while also underscoring the need to strengthen both levels to improve teachers’ decision-making, financial stability, and their role in educating students about financial matters.